Identification of Home Base Business Management as a Full-Time Job in Indonesia - Faqih Nabhan; Yuli Purbaningsih; Ahmad Ridwan; Ita Nurcholifah; Prasetyono Hendriarto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Often people think that the home-based business is a side job and does not have the potential for success like other full-time jobs involved in other companies and business entities. To prove home base to be a full-fledged job that brings success, we have obtained data from an online collection of hundreds of scientific papers published by leading journals and publications such as Google Book, Elsevier, sage pub, Springer, Taylor & France, and Academic Press. To keep data from publications up to date, we target articles published between 2010 and 2021. Next, we examined the data using a coding, interpretation, and in-depth evaluation system with a phenomenological approach. Based on the evidence from the study and discussion of the data findings, we can say that work from home is an alternative career where there is no need for travel, can work remote which has free time and is usually less constrained, resulting in more tangible productivity gains and flexibility compared to working from outside the home in the company. If it is done in a business way, it will be possible to earn profits as a home business and even exceed the benefits of working outside the home. Thus, the results of the study will be helpful in the development of future business science by both academics and practitioners.